Investigation on the Textural Properties Tuning of Ordered Mesoporous Carbons with an Excellent Electrochemical Performance. (9th October 2011) - Srinivasu, Pavuluri
Abstract : A synthetic method to produce mesoporous carbons with tunable textural properties and ordered pore structure has been developed by changing sucrose to water ratio. The specific surface area of 1437 m 2 /g with pore volume of 1.4 cm 3 /g and porosity of mesopores centered at around 4.4 nm are achieved by tuning the concentration of filling amount into mesoporous silica. The mesoporous carbon exhibits hexagonal rod-like morphology (a diameter of 1.2 μ m), which confirms that the replication process is highly successful. It is demonstrated that the prepared mesoporous carbon exhibits much higher current density and superior performance as compared to conventional activated charcoal.